Hypertension in Women: A South-Asian Perspective - Farrukh, Fatima; Abbasi, Amin; Jawed, Misbah; Almas, Aysha; Jafar, Tazeen; Virani, Salim S.; Samad, Zainab (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Hypertension is an important contributor to cardiovascular disease related morbidity and mortality. Despite the magnitude of its negative impact on cardiovascular outcomes, treatment and control of hypertension remain suboptimal in both men and women. Methods: Numerous databases i.e. PubMed, ScienceDirect, etc. were searched using keywords to identify relevant studies to our narrative review. The findings from the most pertinent articles were summarized and integrated into our narrative review on hypertension in women. Result: The pathophysiology of essential hypertension is still being delineated in both men and women; there are multiple sex specific factors in association with the development of hypertension in women, including age, combined oral contraceptives (COCs), polycystic ovarian syndrome (PCOS), preeclampsia, etc. There are several sex specific considerations in antihypertensives drug choices. Discussion: Despite the magnitude of its negative impact on cardiovascular outcomes, treatment and control of hypertension remain suboptimal in women. Medical treatment and adherence is uniquely challenging for South Asian women due to a variety of socio-cultural-economic factors. Further research is warranted to identify optimal sex-specific treatment options that will improve the control of hypertension and decrease the risk of subsequent cardiovascular disease in both genders.